Postharvest quality of Aster ericoides after treatment with silver thiosulphate and sucrose - Lopes Pivetta, Kathia Fernandes [UNESP]; Machado Mattiuz, Claudia Fabrino; Melo, Regina Ferreira de [UNESP]; Gimenes, Renata [UNESP]; Romani, Gustavo de Nobrega [UNESP]; Batista, Gisele Sales [UNESP] (Univ Federal Santa Maria, 2018)
Aster (Aster ericoides L.) is a flower crop of North American origin, which belongs to the family Asteraceae. This plant presents capitulum-type inflorescences, widely used as cut flowers. In Brazil, it has been grown only recently but still has a high expansion potential. In floriculture, pulsing and conditioning solutions are often used to extend the vase life of cut flowers. The present study aimed to evaluate the influence of silver thiosulphate (STS) pulsing and sucrose solutions on the postharvest life of A. ericoides stems. The experiment was carried out under a complete randomized design with treatments arranged in a 2x5 factorial scheme. Treatments consisted of flower stems treated with STS pulsing for 30 minutes, combined with four sucrose concentrations (5, 10, 15, and 20%) for six hours, plus a control (without treatment). Each plot contained four replicates of 10 stems, totalizing 400 stems. The following variables were daily: vase life, fresh mass, and relative water content (RWC). For pulsing data, means were compared by the Tukey's test (p >= 5%). Yet for sucrose concentrations, means were submitted to a polynomial regression to verify, the behavior of variables as a function of concentrations increases. Likewise, each treatment was evaluated for fresh mass and RWC variations over time by a polynomial regression. Results indicated no effect of STS pulsing (2mM) on the vase-life length of aster stems. In contrast, the sucrose solution at 10% extended the vase life of stems by two days, decreased fresh mass loss, and helped maintain water balance in stems.
Keywords: water relations; vase life; pulsing; aster